1999
DOI: 10.1063/1.873607
|View full text |Cite
|
Sign up to set email alerts
|

Oblique collision of modified Korteweg–de Vries ion-acoustic solitons

Abstract: Two-dimensional propagation and oblique collision of modified Korteweg–de Vries (mKdV) ion-acoustic solitons in a plasma with negative ions have been investigated experimentally. At a critical concentration of negative ions, both compressive and rarefractive mKdV solitons exhibit a resonance interaction at a particular amplitude when the colliding angle is fixed. The amplitude is found to be equal for both compressive and rarefractive solitons. The collided solitons suffer a positive phase shift during the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…The selected parameters values are inspired by the recorded recent experimental data of multicomponent plasma experiments [21][22][23][24]28], though we focus on the case of heavier negative ion magnetized multicomponent plasma Ar + -SF Figure 1 shows the oblique collision of two nonlinear IASWs which results as rarefaction of negative ion number density. It is shown that when two IASWs obliquely collide, a new nonlinear wave is formed during their collision (i.e., blue region) which moves ahead of the colliding IASWs; both its amplitude and width are larger than those of colliding IASWs, as depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected parameters values are inspired by the recorded recent experimental data of multicomponent plasma experiments [21][22][23][24]28], though we focus on the case of heavier negative ion magnetized multicomponent plasma Ar + -SF Figure 1 shows the oblique collision of two nonlinear IASWs which results as rarefaction of negative ion number density. It is shown that when two IASWs obliquely collide, a new nonlinear wave is formed during their collision (i.e., blue region) which moves ahead of the colliding IASWs; both its amplitude and width are larger than those of colliding IASWs, as depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Negative ions have been detected in the Earth's ionosphere [18], cometary comae [19], and the upper regions of Titan [20]. Moreover, multicomponent plasmas, such as Ar/SF 6 and K/SF 6 plasmas, are generally used to perform basic research on IASWs in dc discharge devices and Q-machines [21][22][23][24][25][26][27][28]. Since the early space observations [29], it has been admitted that the Maxwellian distribution is not always a realistic distribution [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we know that one of the striking properties of solitons is their asymptotic preservation of form when they undergo a collision, as was first remarked by Zabusky and Kruskal (1965). For the collision of solitary waves, the solution of two solitary waves of two Kortewege-de Vries (KdV) equations, which are valid for long waves, can explain the resonance phenomena, which have been observed in the laboratory in shallow water wave experiments (Maxworthy 1980), in plasma experiments (Nakamura et al 1999), in two-core optical fiber (Tsang et al 2004) and in fluid-filled elastic tubes (Demiray 2005). Some authors (Demiray 2005;Su and Mirie 1980) have studied the head-on collision of solitary waves in different media by using the extended Poincaré-Lighthill-Kuo (PLK) perturbation method (Jeffery and Kawahawa 1982).…”
mentioning
confidence: 93%
“…Plasmas containing a fraction of negative ions possess characteristic dynamical properties that may differ substantially from those of "traditional" (textbook) electronion plasmas. Such plasmas have been generated in the laboratory by using a Q-machine [7,8], a double plasma device [9][10][11], electron cyclotron resonance (ECR) based plasma devices [12,13] and specially designed discharge chambers [14]. Negative ion plasmas (NIP) have also been observed in Space environments, e.g.…”
Section: Introductionmentioning
confidence: 99%